Pelayanan Keagamaan Jemput Bola oleh Kantor Wilayah Kementerian Agama Kepulauan Riau di Wilayah Hinterland Kepulauan Riau - Febriana, Andi (POKJANAS Bekerja Sama Biro Perencanaan dan Penganggaran, Sekretariat Jenderal Kementerian Agama RI, 2024)
The Ministry of Religious Affairs of Regional Office of the Riau Islands continues to strive to improve services to communities in the hinterland region with a pick-up and drop-off program. This program aims to bring services closer to the community, facilitate access to services, and improve service quality. The types of services available include Hajj and Umrah registration, marriage registration, legalization of marriage certificates, guidance on Hajj rituals, religious counseling, zakat and endowment services, and religious education. The service method used is by sending officers and mobile cars to the hinterland area and collaborating with the local government. This paper uses a qualitative method with an approach to literature study and interviews in the field. The results show that this program is beneficial for the community because they no longer need to travel long distances to get Ministry of Religious Affairs services, thereby saving time and money. This program still faces several challenges, such as the vast and remote hinterland area, limited infrastructure, and lack of human resources. The Ministry of Religious Affairs of Regional Office of the Riau Islands continues to strive to improve the quality of this program. The ball pick-up program is the right effort to improve services to communities in the hinterland region and is expected to provide benefits to communities in the region.